Knockout mice in understanding the mechanism of action of lithium. (21st September 2009) - Agam, Galila; Bersudsky, Yuly; Berry, Gerard T.; Moechars, Diederik; Lavi-Avnon, Yael; Belmaker, R.H.
Abstract : Lithium inhibits IMPase (inositol monophosphatase) activity, as well as inositol transporter function. To determine whether one or more of these mechanisms might underlie lithium's behavioural effects, we studied Impa1 (encoding IMPase) and Smit1 (sodium– myo -inositol transporter 1)-knockout mice. In brains of adult homozygous Impa1 -knockout mice, IMPase activity was found to be decreased; however, inositol levels were not found to be altered. Behavioural analysis indicated decreased immobility in the forced-swim test as well as a strongly increased sensitivity to pilocarpine-induced seizures. These are behaviours robustly induced by lithium. In homozygous Smit1 -knockout mice, free inositol levels were decreased in the frontal cortex and hippocampus. These animals behave like lithium-treated animals in the model of pilocarpine seizures and in the Porsolt forced-swim test model of depression. In contrast with O'Brien et al. [O'Brien, Harper, Jove, Woodgett, Maretto, Piccolo and Klein (2004) J. Neurosci. 24, 6791–6798], we could not confirm that heterozygous Gsk3b (glycogen synthase kinase 3β)-knockout mice exhibit decreased immobility in the Porsolt forced-swim test or decreased amphetamine-induced hyperactivity in a manner mimicking lithium's behavioural effects. These data support the role of inositol-related processes rather than GSK3β in the mechanism of the therapeutic action of lithium.